Prácticas y desafíos del uso de Twitter/X como fuente periodística en Latinoamérica - Medrano Bonilla, Daniela; Portocarrero Hurtado, Liz Mariam; Cobos, Tania Lucía (Folios, revista de la Facultad de Comunicaciones y Filología, 2025)
Twitter/X is one of the most used platforms to generate, exchange and disseminate information among journalists. Through an online survey with a mixed approach and descriptive scope conducted between June and September 2023, the practices and challenges of Latin American journalists were explored, taking into account aspects such as frequency of use, ease of access, criteria of trust in a source and risks. Among the 165 valid responses, the perception that Twitter/X has facilitated access to information sources and experts prevailed. The results indicate that, although challenges remain, a large percentage consider it a key tool in the digital sphere due to its immediacy and ease of access.